2020
DOI: 10.1371/journal.pone.0236675
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care unit patients’ opinion on enrollment in clinical research: A multicenter survey

Abstract: Background In most emergency situations or severe illness, patients are unable to consent for clinical trial enrollment. In such circumstances, the decision about whether to participate in a scientific study or not is made by a legally designated representative. Objective To address the willingness of patients admitted to the intensive care unit (ICU) to be enrolled in a scientific study as volunteers, and to assess the agreement between patients' and their legal representatives' opinion concerning enrollment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Patients and HCPs were supportive of data being used in the case of patient death or up until the point of declining to continue in a study [ 26 , 35 , 38 , 50 ]. While this preserves the validity of trial results by preventing selection bias, ethical questions are raised on whether families should be informed of their relatives’ inclusion after death.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Patients and HCPs were supportive of data being used in the case of patient death or up until the point of declining to continue in a study [ 26 , 35 , 38 , 50 ]. While this preserves the validity of trial results by preventing selection bias, ethical questions are raised on whether families should be informed of their relatives’ inclusion after death.…”
Section: Discussionmentioning
confidence: 90%
“…Participants were generally accepting of the use of deferred consent [ 25 , 26 , 29 , 30 , 32 , 35 , 36 , 38 , 40 , 41 , 43 45 , 47 , 49 , 50 ]. However, even in studies reporting positive views, a wide range of acceptability was observed (50–95.6%) [ 36 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations